Building automation systems: Concepts and technology review - Domingues, Pedro; Carreira, Paulo; Vieira, Renato; Kastner, Wolfgang (Computer standards and interfaces, 2016)
Despite the popularity of the subject, one surprising aspect of building automation (BA) is the scarcity of authoritative literature references regarding the topic. This situation hampers communication between developers and contributes to the well-known problem of heterogeneity where there is difficulty in integrating solutions from different manufacturers with each other. This article systematizes fundamental concepts and requirements of BA systems, defining each aspect based upon established literature standards. Using these aspects as guidelines, the main BA technology specifications available are then reviewed with respect to their coverage of features. We then proceed by showing that none of the analyzed specifications are able to totally cover the expected standard functionality span of BA. Finally, we conclude that none of the existing approaches are able to fully overcome the problem of heterogeneity by satisfactorily addressing all the aspects of BA endorsed by the standards. •Fundamental concepts of BAS are reviewed and unified.•The coverage of functionality by existing automation technologies is assessed in the light of ISO and European standards.•The main solutions to interoperability arising from BA from technologies are analyzed and compared.